2018
DOI: 10.1016/j.ijppaw.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Toxoplasma gondii isolates obtained from free-living wild birds rescued in Southeastern Brazil

Abstract: Recent studies carried out in Brazil have shown that strains from the same Toxoplasma gondii genotype can infect humans, domestic animals (dogs and cats) and animals slaughtered for human consumption (pigs, sheep, goats, and chickens), suggesting a common infection route. However, little is known about the importance of free-living wild birds within this epidemiological context. The objective of this work was to isolate, genotype, and evaluate the virulence for mice of new isolates of T. gondii obtained from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
15
0
2
Order By: Relevance
“…Although important for other inferences, such as strain determination, we also found that parasite isolation methods were less sensitive for detecting infections. Failure of detection can occur if tissue cysts are very small and/or are not included in the sampled tissue, and although T. gondii has a predilection for the brain and the heart, the success of isolation can differ between these tissues even within the same individual (Rêgo et al, 2018), possibly owing to varying stages of infection (Ingram, Goodrich, Robey, & Eisen, 2013). Although seroreversion and detection failure decrease prevalence estimates, this influence should be equal across species regardless of trophic guild, habitat or scavenging tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Although important for other inferences, such as strain determination, we also found that parasite isolation methods were less sensitive for detecting infections. Failure of detection can occur if tissue cysts are very small and/or are not included in the sampled tissue, and although T. gondii has a predilection for the brain and the heart, the success of isolation can differ between these tissues even within the same individual (Rêgo et al, 2018), possibly owing to varying stages of infection (Ingram, Goodrich, Robey, & Eisen, 2013). Although seroreversion and detection failure decrease prevalence estimates, this influence should be equal across species regardless of trophic guild, habitat or scavenging tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii was isolated from six of the 44 birds. Rêgo et al (2018) genotyped these isolates and identified five different genotypes by PCR-RFLP. A unique genotype, not previously described was common to two isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Toxoplasma genotypes produce different degrees of virulence in humans and mice (Xiao & Yolken, 2015), and given the high diversity recently found in Central and South America (Ajzenberg et al, 2004;Lehmann et al, 2004;Rajendran et al, 2012;Vitaliano et al, 2014;Rego et al, 2018;Vethencourt et al, 2019) the observed differences in seroprevalence between wild and captive NP might be due to different genotypes. Little is known about the genotypes circulating in wildlife, and associations between strain type, lesion patterns and clinical outcome have not been reported in wildlife frequently.…”
Section: Discussionmentioning
confidence: 99%